Integral Analysis of Seismic Refraction and Ambient Vibration Survey for Subsurface Profile Evaluation - Z. A. M., Hazreek; A. F., Kamarudin; S., Rosli; A., Fauziah; M. A. K., Akmal; M., Aziman; A. T. S., Azhar; M. I. M., Ashraf; M. Z. N., Shaylinda; Y., Rais; M. F., Ishak; M. N. A., Alel (IOP Publishing, 2018)
Geotechnical site investigation as known as subsurface profile evaluation is the process of subsurface layer characteristics determination which finally used for design and construction phase. Traditionally, site investigation was performed using drilling technique thus suffers from several limitation due to cost, time, data coverage and sustainability. In order to overcome those problems, this study adopted surface techniques using seismic refraction and ambient vibration method for subsurface profile depth evaluation. Seismic refraction data acquisition and processing was performed using ABEM Terraloc and OPTIM software respectively. Meanwhile ambient vibration data acquisition and processing was performed using CityShark II, Lennartz and GEOPSY software respectively. It was found that studied area consist of two layers representing overburden and bedrock geomaterials based on p-wave velocity value (vp = 300 – 2500 m/s and vp > 2500 m/s) and natural frequency value (Fo = 3.37 – 3.90 Hz) analyzed. Further analysis found that both methods show some good similarity in term of depth and thickness with percentage accuracy at 60 – 97%. Consequently, this study has demonstrated that the application of seismic refractin and ambient vibration method was applicable in subsurface profile depth and thickness estimation. Moreover, surface technique which consider as non-destructive method adopted in this study was able to compliment conventional drilling method in term of cost, time, data coverage and environmental sustainaibility.